2009
DOI: 10.3844/ajassp.2009.1301.1307
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Fusarium Oxysporum F. Sp. Cubense of Banana

Abstract: Problem statement: Morphological characterization of Fusarium species which emphasize on microscopic and cultural characteristics are not sufficient to characterize Fusarium Oxysporum F. sp. Cubense (FOC) from banana as these characteristics could easily influence by environmental factors. As an alternative molecular methods were used to characterize and to assess genetic variation of FOC from different banana cultivars. Knowledge on the genetic variation is important to determine the genetic relationship betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 12 publications
0
15
0
1
Order By: Relevance
“…Sugeriram ainda que esta variação genética poderia ser devido à adaptação e coevolução do fungo com o hospedeiro e com os fatores ambientais do local. Leong et al (2009) …”
Section: Resultsunclassified
“…Sugeriram ainda que esta variação genética poderia ser devido à adaptação e coevolução do fungo com o hospedeiro e com os fatores ambientais do local. Leong et al (2009) …”
Section: Resultsunclassified
“…ciceris species recovered from wilted chickpea plants using ITS-1 and ITS-4 species specific primers and sequenced. Similarly, other studies carried out by Leong et al (2009), Dissanayake et al (2009), Palmore et al (2010, Chehri et al (2011) on identification of different Fusarium species using ITS-rDNA as a molecular marker provide evidences that this marker was helpful for the identification of Fusarium species. Our findings corroborate with these studies, which confirmed that ITS-rDNA markers can be used for the rapid and accurate identification of Fusarium species.…”
Section: Upgma Analysismentioning
confidence: 99%
“…Banana (Musa sapientum) is susceptible to the infection by several fungal diseases of which Fusarium-wilt caused by F. oxysporum is considered to be the most important and responsible for severe economic losses in bananaproducing countries (Butler 2013;Moretti et al 2004). Leong et al (2009) also reported the infection caused by F. oxysporum in banana and successfully isolated 13 isolates of F. oxysporum from Malaysia and two isolates from Indonesia. Recently, Triest et al (2016) reported that F. musae was responsible for the infection of banana fruits and the consumption of such infected fruits may cause fusariosis in human being.…”
Section: Introductionmentioning
confidence: 99%
“…cubense (FOC) is a serious vascular disease. The pathogen is divided into four races based on differences in pathogenicity on Musa cultivars; race 4 is ranked as the most virulent race and can infect all Cavendish cultivars1. Fusarium oxysporum can survive for long periods in the absence of the host, mainly in the form of thick-walled chlamydospores.…”
mentioning
confidence: 99%